Pengembangan LKPD Kontekstual Berbantuan Zep Quiz Untuk Meningkatkan Kemampuan Literasi Matematis dan Motivasi Belajar - Trisnavia, Vivi; Imswatama, Aritsya; Lukman, Hamidah Suryani (Jurnal PEKA (Pendidikan Matematika), 2026)
The purpose of the development of the Contextual Learning Activity Sheet (LKPD) with Zep Quiz is to improve mathematical literacy and learning motivation. The research subject is eighth grade students at SMP PGRI Caringin, with the subject of study being statistics. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection techniques used include interviews, expert validation, survey distribution, testing, and documentation. The results of this study are as follows: (1) The expert validation was performed by the subject matter and media experts. The expert content validation received a score of 91%, while the expert media validation received a score of 94%, both of which are considered "valid". (2) The practicality of the teaching materials includes the survey responses of teachers and students. The results obtained from the teacher survey were 100%, while the results obtained from the student survey were 84%. Both survey results had a "very practical" criterion. (3) The effectiveness of the instructional material was obtained from the data from the pretest-posttest and the motivation learning survey before and after the intervention using N-Gain. Both data sets received a "moderate" category with a pretest-posttest N-Gain of 0.47 and a motivation learning survey N-Gain of 0.33